The Role of Transformational Leadership and Communication in Community-based Tourism: The Case of Dieng Culture Festival - Kusumastuti, Retno Dyah (Prisani Cendekia Institute, 2024)
Community-based tourism is conceived as a bottom-up tourism management, centered and managed by the local community. Dieng Culture Festival is a tourism event established by the local community in line with the community-based tourism concept. The establishment of this event is possible with transformational leadership and extensive communication performed by the founder of the Dieng Culture Festival and Pokdarwis Dieng Pandawa, Mr. Alif Faozi. This research aims to investigate further the role of transformational leadership and communication in the establishment of the Dieng Culture Festival. This research utilized a qualitative and descriptive approach through the perspective of Mr. Alif Faozi. The findings of this research are that the role of transformational leadership and extensive communication is instrumental in the establishment and success of the Dieng Culture Festival. This is because transformational leadership and extensive communication are essential to building strong community participation and providing resources and knowledge from the Dieng local community and external parties that enabled the establishment and success of the Dieng Culture Festival. This research implies that tourism events could also be successfully established by local communities in line with community-based tourism. This could be achieved through strong local leadership and extensive communication with the local community members and external parties.